Pengujian Website Bursa Kerja Khusus SMK Negeri 1 Surabaya Menggunakan Web Based Application Quality Model - Ardina Fitri Haryono; Bayu Priyambadha; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SMK Negeri 1 Surabaya is one of school which has Its own job market that aim to inform such as apply a job, counseling about positioning and distribution to job market through website. System should have good quality to achieve vision and mision of Job Market of SMK Negeri 1 Surabaya. The purpose of this research is how to evaluate Job Market website of SMK Negeri 1 Surabaya using Web Based Application Quality Model (WBAQM) which has factors on three perspective. Developer perspective has maintainability factor which tested using Maintainability Index (MI), portability factor focused on compatibility website on seven desktop browser and five mobile browser. Visitor perspective has usability, accessibility, and content which tested using WQU (Website Questionnaire Usability). Credibility factor tested using questionnaire by BJ Fogg. Functionality factor tested using validation testing to all existing functionality requirement. Security factor tested using Acunetix Website Vulnerability tool. Owner perspective has differentiation and popularity factors tested by review how good credibility and accessibility website are. The result known that maintainability, portability, and functionality has achieve the expected result. While usability, accessibility, content, credibility, popularity, and differentiation needs some improvement.